2020
DOI: 10.1590/0100-3984.2019.0101
|View full text |Cite
|
Sign up to set email alerts
|

Impact of artificial intelligence on the choice of radiology as a specialty by medical students from the city of São Paulo

Abstract: Abstract Objective: To evaluate the impact of artificial intelligence (AI) on undergraduate medical students’ choice of radiology as a specialty. Materials and Methods: In February 2019, an anonymous online survey was sent to medical students. The research contemplated questions on how much students think they know about AI technologies, how much AI discourages them from choosing radiology as a specialty, and whether they believe there is a threat to the radiology job market. Results: A total of 101… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 10 publications
1
23
1
Order By: Relevance
“…The main results of this study are generally in agreement with previously published studies in Canada, 14 Germany, 19 United Kingdom, 20 Brazil 21 and U.S. 24 which concluded that AI has a negative influence on student choice for radiology. This survey was critical to conduct in our country and is still needed to conduct in other parts of the world, in order to understand if the anxiety towards AI exists and to provide a specific recommendation needed by each country or institute since the recommendations provided by earlier studies (including ours) may not be applicable to different populations.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The main results of this study are generally in agreement with previously published studies in Canada, 14 Germany, 19 United Kingdom, 20 Brazil 21 and U.S. 24 which concluded that AI has a negative influence on student choice for radiology. This survey was critical to conduct in our country and is still needed to conduct in other parts of the world, in order to understand if the anxiety towards AI exists and to provide a specific recommendation needed by each country or institute since the recommendations provided by earlier studies (including ours) may not be applicable to different populations.…”
Section: Discussionsupporting
confidence: 92%
“… 9,14–18 Misunderstanding about the effect of AI on radiology may discourage medical students from considering radiology as a specialty. 14 Previous studies in the same subject from Canada, 14 Germany, 19 UK 20 , and Brazil 21 concluded that AI played a negative role in medical students’ choice for radiology.…”
Section: Introductionmentioning
confidence: 99%
“…However, they also felt that AI will play an integral role in delivering medical services in the future, which may reflect that early teaching about AI in the medical curriculum shall be inculcated to spark an interest in this upcoming field. Several studies had conflicting findings of the perception of medical students about whether AI will replace humans in a medical specialty, here radiology [15,[18][19][20]. Although, in our study, the majority of students agree that AI will not replace physicians in the future, it is recommended to pursue positive efforts in spreading awareness about AI so that misinformation and human hesitancy can be reduced.…”
Section: Discussioncontrasting
confidence: 54%
“…A few other studies have explored the views of medical students on AI including a narrow investigation on specific subspecialties (10,14,30,31). However, the novelty of our work is rooted in our focus on AI in both Medicine and Dentistry rather than in subspeciality such as radiology.…”
Section: Study Position Compared To the Current Body Of Evidencementioning
confidence: 99%